ANALYSIS OF FACTORS AFFECTING OCCURRENCE OF SCHIZOPHRENIA IN CAMPURDARAT PUBLIC HEALTH CENTER - Karina, Zeela (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2018)
Schizophrenia is one type of psychiatric disorder characterized by disruption of the ability to distinguish between real and imaginary nature. According to data from 2018, there is a total of 210 schizophrenic patients who seek treatment at the Campurdarat Public Health Center. Schizophrenia is caused by many factors, including genetic factors, trauma, family structure, family upringing, and tensions due to economic factors. The purpose of this study is to determine the factors that affect the incidence of schizophrenia and the most dominant factor. This research type used desriptive analytic with a case control design. With the entire population of schizophrenic patients aged over 17 years in the  Campurdarat Public Health Center. The sampling technique used random sampling techniques. Bivariate data analysis used logistic regression statistical test and multivariate analysis used multiple logistic regression. Great influence among variables expressed in OR with 95% CI and p = 0.05. Based on bivariate analyzes influential factors were trauma (OR = 5.8, CI 95%; 1.011 to 33.922), family parenting (OR = 14.7, CI 95%; 2.311 to 93.570), and tension due to economic factors (OR = 5.9, 95% CI 1.060 to 32.935). Based on multivariate analysis, the most dominant factor was family parenting (OR = 12.3, CI 95%; 3.888 to 39.151). Highly pathogenic parenting affects the incidence of schizophrenia, so families need to improve family parenting. Non-pathogenic parenting can reduce the risk of the incidence of schizophrenia.